2019
DOI: 10.1089/jwh.2017.6889
|View full text |Cite
|
Sign up to set email alerts
|

Positive Emotions During Infant Feeding and Postpartum Mental Health

Abstract: Background: Research shows that individuals can improve mental health by increasing experiences of positive emotions. However, the role of positive emotions in perinatal mental health has not been investigated. This study explored the extent to which positive emotions during infant feeding are associated with maternal depression and anxiety during the first year postpartum. Materials and Methods: One hundred and sixty-four women drawn from a longitudinal cohort of mother-infant dyads were followed from the thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…The lack of modification of our findings by prenatal psychopathology or infant feeding status at 2 months suggests that the experiential and relational aspects of infant feeding may yield benefits regardless of early postpartum challenges. Therefore, healthcare providers and peer supporters should address the maternal emotional experience of infant feeding regardless of infant feeding method, given the potential benefits for both postpartum mental health (Wouk, Gottfredson et al, 2018) and overall maternal satisfaction with breastfeeding.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of modification of our findings by prenatal psychopathology or infant feeding status at 2 months suggests that the experiential and relational aspects of infant feeding may yield benefits regardless of early postpartum challenges. Therefore, healthcare providers and peer supporters should address the maternal emotional experience of infant feeding regardless of infant feeding method, given the potential benefits for both postpartum mental health (Wouk, Gottfredson et al, 2018) and overall maternal satisfaction with breastfeeding.…”
Section: Discussionmentioning
confidence: 99%
“…For example, one interview study revealed that, although mothers expressed high levels of “relief and pleasure” after using formula, they also experienced significant negative affect (e.g., guilt, sense of failure) and concerns about negative reactions from others, especially health care providers (Lee, 2007). Because the experience of positive emotions during infant feeding is associated with fewer subsequent symptoms of postpartum depression and anxiety (Wouk et al, 2018), stigmatizing formula feeding may exacerbate the risk of developing these conditions. Additionally, evidence suggests that concerns about encountering stigma impede caregivers from receiving adequate information about safe formula feeding practices, potentially undermining parenting confidence during the critical postpartum period and also endangering infants (Hvatum & Glavin, 2016; Lee, 2007; Wirihana & Barnard, 2012).…”
Section: Formula Feeding Stigmamentioning
confidence: 99%
“…[2][3][4][5] Additionally, breastfeeding has protective effects against postpartum depression, anxiety, and optimize stress responses. [6][7][8] Benefits to the infant include a reduced risk of infectious disease, sudden infant death syndrome, or metabolic disease, and higher intelligence scores in young adults. [9][10][11][12] Thus, it is understandable that the American Academy of Pediatrics (AAP), the American College of Obstetrics and Gynecology (ACOG), and the World Health Organization recommend that infants should be exclusively breastfed for 6 months unless there is a contraindication.…”
Section: Introductionmentioning
confidence: 99%
“…Maternal breastfeeding benefits include a reduced risk of breast cancer, ovarian cancer, hypertensive disorder, or diabetes 2‐5 . Additionally, breastfeeding has protective effects against postpartum depression, anxiety, and optimize stress responses 6‐8 . Benefits to the infant include a reduced risk of infectious disease, sudden infant death syndrome, or metabolic disease, and higher intelligence scores in young adults 9‐12 .…”
Section: Introductionmentioning
confidence: 99%